Digital innovation in citizen science to enhance water quality monitoring in developing countries - Pattinson, N. B.; Taylor, J.; Dickens, Chris W. S.; Graham, P. M. (International Water Management Institute, 2023)
Freshwater systems are disproportionately adversely affected by the ongoing, global environmental crisis. The effective and efficient water resource conservation and management necessary to mitigate the crisis requires monitoring data, especially on water quality. This is recognized by Sustainable Development Goal (SDG) 6, particularly indicator 6.3.2., which requires all UN member states to measure and report the ‘proportion of water bodies with good ambient water quality’. However, gathering sufficient data on water quality is reliant on data collection at spatial and temporal scales that are generally outside the capacity of institutions using conventional methods. Digital technologies, such as wireless sensor networks and remote sensing, have come to the fore as promising avenues to increase the scope of data collection and reporting. Citizen science (which goes by many names, e.g., participatory science or community-based monitoring) has also been earmarked as a powerful mechanism to improve monitoring. However, both avenues have drawbacks and limitations. The synergy between the strengths of modern technologies and citizen science presents an opportunity to use the best features of each to mitigate the shortcomings of the other. This paper briefly synthesizes recent research illustrating how smartphones, sometimes in conjunction with other sensors, present a nexus point method for citizen scientists to engage with and use sophisticated modern technology for water quality monitoring. This paper also presents a brief, non-exhaustive research synthesis of some examples of current technological upgrades or innovations regarding smartphones in citizen science water quality monitoring in developing countries and how these can assist in objective, comprehensive, and improved data collection, management and reporting. While digital innovations are being rapidly developed worldwide, there remains a paucity of scientific and socioeconomic validation of their suitability and usefulness within citizen science. This perhaps contributes to the fact that the uptake and upscaling of smartphone-assisted citizen science continues to underperform compared to its potential within water resource management and SDG reporting. Ultimately, we recommend that more rigorous scientific research efforts be dedicated to exploring the suitability of digital innovations in citizen science in the context of developing countries and SDG reporting.